A presença da Literatura Africana lusófona no livro didático de Língua Portuguesa do 3º ano do Ensino Médio (PNLD 2012 – 2015): uma reflexão histórica, social e literária - Almeida, Patricia Caldeira de (2017)
The present research investigates the content of the discipline Lusophone African Literature present in the Portuguese Language textbooks of the 3rd year of High School, reflecting on the contribution of content to the recognition and reparation of social and racial inequalities in Brazilian society, for the dignified formation of the citizen; for the promotion of a fairer and more egalitarian society; to reduce prejudice and discrimination. It will be used as corpus textbooks from two specific moments: when the content was made mandatory through the "PNLD Guide (National Guidance for the Didactic Book) of 2012" and in 2015, at the beginning of the preparation of this study, twelve years after the Law No. 10,639 to be sanctioned. This study is justified by the racial configuration of the Brazilian people, with 50.76% calling themselves blacks and browns according to the IBGE Demographic Census of 2010 in a society that is still racist and discriminatory in several of its social practices, also present at school, in several of its social practices and reflected in textbooks. This study starts with the concept of Literature as a tool to encourage reflection on Brazilian cultural identity, broadening student horizons, discussing diversity, and therefore cooperating with Law 10.639 / 2003